Song - As A Key To Awakening Interest In The Russian Language - Nasyrova Nargiza Akhmetovna (Euro Asian Journal Publishing, 2024)
In the article, the author describes an idea that can solve teaching and educational goals at the same time. The article is devoted to the study of modern popular songs and songs from films for the possibility of their use in Russian as a foreign language (RFL) lessons as educational material. The material is interesting and useful to those who are looking for something new and want to make their contribution to spiritual development. The author calls for joining forces, hoping that the proposed experience will be taken up by colleagues from other cities.
Keywords: development of memory; creation of language didactic material; interest in learning; song as small genre of verbal creativity with huge possibilities